Orientation Mapping of Extruded Polymeric Composites by Polarized Micro-Raman Spectroscopy - Xiaoyun Chen; M. Anne Leugers; Tim Kirch; Jamie Stanley (Journal of Spectroscopy)
Molecular orientation has a strong influence on polymeric composite materials’ mechanical properties. In this paper we describe the use of polarized micro-Raman spectroscopy as a powerful tool to map out the molecular orientation of a uniaxially oriented polypropylene- (PP-) based composite material. Initial samples exhibited a high degree of surface fibrillation upon cutting. Raman spectroscopy was used to characterize the degree of orientation in the skin and guide the development of the posttreatment process to optimize the skin relaxation while maintaining the high degree of orientation in the rest of the board. The PP oriented polymer composite (OPC) was oriented through an extrusion process and its surface was then treated to achieve relaxation. Micro-Raman analysis at the surface region demonstrated the surface orientation relaxation, and the results provide an effective way to correlate the extent of relaxation and process conditions. Larger scale orientation mapping was also carried out over the entire cross-section (12.7 cm × 2.54 cm). The results agree well with prior expectation of the molecular orientation based on the extrusion and subsequent quenching process. The methodologies described here can be readily applied to other polymeric systems.